POVERTY AS A BARRIER TO THE ACHIEVEMENT OF THE RIGHT TO HEALTH - Revita Pirena Putri; Wiwik Afifah; Tomy Michael (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The problem of economic weakness, which until now hasn’t been resolved, creates conditions for the inability of the community to fulfill their welfare. The welfare includes the right to live a decent life, the right to obtain health, and the right to education. People’s welfare should be the responsibility of the states as the bearer of the obligation to fulfill the rights of every citizen. The right to health that is not fulfilled is a form of human rights violations. Because basically health is a pillar of a nation’s development. Health becomes a basic need for every human being. Judging from the many cases that occur in society as a result of the unfulfilled welfare, especially in terms of economy and health. So the author, in this case the author is interested in studying these problems by taking the case of Baby Deborah. The research method that the author uses is normative juridical, using law as the basis for research. In this case the writer also uses descriptive research method in the Longitudinal way. The data used are sourced from events in the community, as well as supporting statistical data. So from this research, it can lead to a conclusion that the people’s welfare should be the responsibility of the state. This is as stated in the 1945 Constitution of the Republic of Indonesia and is also contained in the International Economic, Social and Culture Convention. If the state is unable to create such prosperity, then the state is considered negligent and violates the human rights of its citizens. So from not achieving this welfare, there will be many rights that aren’t achieved, one of which is the right to health.